A flocculant for sewage treatment and preparation method thereof

A flocculant made from modified polyaluminium chloride, cross-linked sepiolite, and modified sodium alginate addresses the inefficiencies of existing flocculants by enhancing adsorption and bridging effects, achieving effective flocculation and metal ion fixation in wastewater treatment.

CN118307103BActive Publication Date: 2024-12-27HUIZHOU LVKE ENVIRONMENTAL PROTECTION CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410488582.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-23
Publication Date
2024-12-27
Estimated Expiration
2044-04-23

AI Technical Summary

Technical Problem

Existing flocculants used in water treatment, such as inorganic, synthetic organic, and natural polymer flocculants, suffer from issues like loose flocs, metal residues, unstable structures, monomer residues, and limited molecular weight, leading to ineffective flocculation and secondary pollution.

Method used

A flocculant composed of modified polyaluminium chloride, cross-linked sepiolite, and modified sodium alginate, with specific preparation methods to enhance adsorption, bridging, and chelation effects, forming dense flocs and stabilizing heavy metal ions.

Benefits of technology

The flocculant achieves enhanced flocculation by adsorbing organic pollutants, compressing colloidal layers, and forming stable chelates, resulting in improved sedimentation and reduced residual metal ions, with high efficiency in wastewater treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FHA0000008537850000011
    Figure FHA0000008537850000011
  • Figure GDA0005157898440000021
    Figure GDA0005157898440000021
  • Figure GDA0005157898440000051
    Figure GDA0005157898440000051
Patent Text Reader

Abstract

The invention relates to the technical field of water treatment, and discloses a flocculant for sewage treatment and a preparation method thereof. The flocculant is formed by mixing modified polyaluminium chloride, cross-linked sepiolite and modified sodium alginate as main raw materials through ball milling. In the flocculation process, the cross-linked sepiolite with a large specific surface area in the flocculant adsorbs organic pollutants in the wastewater, so that the pollutants are gathered around the flocculant, and the concentration of pollutants around the flocculant is increased. Then, the metal cations in the modified polyaluminium chloride attract the particles and also play a role in compressing the negatively charged colloid double layer. The chitosan macromolecule can play a bridging role. The modified sodium alginate can adsorb and chelate heavy metal ions to form a stable chelate, thereby reducing the residual metal ions. The components cooperate with each other, so that the flocculant has an excellent flocculation effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water treatment, and in particular to a flocculant for sewage treatment and a preparation method thereof. Background Art

[0002] With the rapid development of industrial production and the rapid improvement of human living standards, water pollution problems are becoming increasingly serious, and have gradually attracted more and more attention, and have gradually become an important factor restricting social development. Therefore, it is urgent to develop efficient water treatment materials to deal with the current water pollution problem. The flocculation process is the most commonly used water purification technology and an indispensable key link in the water treatment process. The core of the flocculation method is to use flocculants to destabilize and aggregate various solutes, suspended particles or colloids in sewage to form flocs, and then accelerate sedimentation to produce a solid-liquid separation effect.

[0003] At present, the flocculants used in water treatment include inorganic salt flocculants, inorganic polymer flocculants, synthetic organic polymer flocculants and natural organic polymer flocculants. Since the flocs produced by inorganic flocculants are relatively loose, easy to break, and easy to produce metal residues, there are major defects in practical applications. The defects of synthetic organic polymer flocculants are mainly unstable structures, and monomer residues will also cause secondary pollution. The molecular weight of natural polymer flocculants is limited, and the flocculation effect is not good. Therefore, it is of great significance to develop high-efficiency flocculants.

[0004] The invention patent with application number CN201710389153.3 discloses a composite flocculant for sewage treatment. A hyaluronic acid polymer containing a dopamine structure is prepared and compounded with chitosan to form a composite flocculant, which exhibits excellent flocculation effect. Therefore, starting from the formula of the flocculant, the components of the flocculant can be adjusted, and the synergistic effect between the components can be utilized to prepare a flocculant with high-efficiency flocculation effect.

[0005] Based on this, the present invention provides a flocculant that can be directly used in the field of sewage treatment and has an excellent flocculation effect. Summary of the invention

[0006] The purpose of the present invention is to provide a flocculant for sewage treatment and a preparation method thereof, and to obtain a flocculant with a high-efficiency flocculation effect by adjusting the formula of the flocculant.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A flocculant for sewage treatment is prepared from the following raw materials in parts by weight:

[0009]

[0010] The preparation method of the flocculant comprises the following steps:

[0011] The first step is to weigh each raw material according to weight and set aside;

[0012] The second step is to put the modified polyaluminium chloride, cross-linked sepiolite and modified sodium alginate into a mixer, stir and mix them evenly, transfer them into a ball mill, add polyoxyethylene polyoxypropylene ether and water, perform wet ball milling and mixing, discharge the materials, and dry them to obtain a flocculant.

[0013] A flocculant for sewage treatment is prepared by the above preparation method.

[0014] Furthermore, the specific preparation method of the modified polyaluminium chloride is as follows:

[0015] Step S1, adding 3-glycidyloxypropyltrimethoxysilane to a hydrochloric acid solution with a mass fraction of 5%, hydrolyzing for 6-9 hours, adding polyaluminium chloride, adjusting the pH to 9-10 with sodium hydroxide solution, stirring at 60-70° C. for 4-6 hours, discharging the material to obtain an intermediate material;

[0016] Step S2, mixing the intermediate material, chitosan and 1-2% acetic acid solution by mass, mechanically stirring evenly, turning on the heating, and when the temperature rises to 50-60° C., keeping the temperature unchanged, stirring for 2-4 hours, cooling and discharging the material, and then obtaining modified polyaluminium chloride.

[0017] Specifically, firstly, 3-glycidyloxypropyltrimethoxysilane is used to modify the surface of polyaluminium chloride to obtain polyaluminium chloride with surface modified with active epoxy groups, i.e., intermediate material. In step S2, since chitosan contains substituted primary amine groups in its structure, it can react with the active epoxy groups of the intermediate material by ring-opening addition, thereby modifying the macromolecular chitosan on the surface of polyaluminium chloride to form polyaluminium chloride with a "star-shaped" structure, i.e., modified polyaluminium chloride.

[0018] Furthermore, in step S1, the concentration of the sodium hydroxide solution is 0.1-0.2 mol / L.

[0019] Furthermore, in step S2, the molecular weight of the chitosan is 400,000-500,000, and the degree of deacetylation is 80-95%.

[0020] Furthermore, the preparation method of the cross-linked sepiolite is as follows:

[0021] Step SS1, adding a sodium hydroxide solution with a concentration of 0.2-0.4 mol / L dropwise to an aluminum chloride solution with a concentration of 0.3-0.5 mol / L, stirring at room temperature for 2-4 hours, and aging at room temperature for 12-24 hours to obtain a crosslinking agent mixture;

[0022] Step SS2, placing the sepiolite in a tubular furnace, calcining it at a temperature of 400-450°C for 1-2 hours, taking it out, allowing it to cool naturally, adding it to the cross-linking agent, controlling the temperature to 60-70°C, mechanically stirring it for 1-3 hours, stopping heating, cooling it to room temperature, and standing it for hydrolysis for 12-18 hours to obtain cross-linked sepiolite.

[0023] Specifically, since the aqueous solution of aluminum chloride can be hydrolyzed under alkaline conditions to produce hydroxyaluminum polymerized cations with large volume and high charge, the polymerized cations can undergo ion exchange with the cations between the sepiolite layers to form cross-linked sepiolite. After the ion exchange, the intercalation effect of the cross-linking agent will cause the distance between the sepiolite layers to be enlarged, thereby increasing the specific surface area of ​​the sepiolite, increasing the ion exchange capacity, and increasing the contact area with the colloidal particles, which is beneficial to the adsorption of pollutants in the wastewater, thereby improving the flocculation effect of the flocculant.

[0024] Furthermore, in step SS2, the solid-liquid ratio of the sepiolite and cross-linking agent mixed solution is 1 g:10-15 mL.

[0025] Furthermore, the preparation method of the modified sodium alginate is as follows:

[0026] Sodium alginate and purified water are stirred and mixed to form a uniform solution, and then the composite catalyst is added to the solution, stirred at room temperature for 20-40 minutes, and then dimethylpyridylamine is added to the solution. After the addition is completed, mechanical stirring is performed for 3-6 hours, and the material is discharged and separated to obtain modified sodium alginate.

[0027] Specifically, under the action of the composite catalyst, sodium alginate can condense with the secondary amine in the dimethylpyridinamine structure, thereby introducing the dimethylpyridinamine structure with a strong chelating effect into the sodium alginate structure to obtain modified sodium alginate. The synergistic effect of sodium alginate and the chelating functional group is utilized to effectively enhance the adsorption and fixation effect of the flocculant on heavy metal ions in the wastewater.

[0028] Furthermore, the composite catalyst is dicyclohexylcarbodiimide and N-hydroxysuccinimide in a mass ratio of 1:0.3-0.4.

[0029] Beneficial effects of the present invention:

[0030] The invention prepares a flocculant with excellent flocculation effect by adjusting the formula of the flocculant. In the flocculation process, the cross-linked sepiolite with a large specific surface area can adsorb organic pollutants in the wastewater, so that the pollutants are gathered around the flocculant, and the concentration of pollutants around the flocculant is increased. Then the metal cations in the modified polyaluminium chloride attract the particles, and at the same time can also play a role in compressing the negatively charged colloid double layer, and the "star-shaped" chitosan macromolecules on the surface can show a spatial network structure, effectively play a bridging role, complement each other, produce adsorption-bridging dual effects, greatly enhance the flocculation effect of the flocculant, and this special shape is easier to form macromolecular clusters, and then form dense flocs, showing excellent flocculation effect. In the flocculation process, the modified sodium alginate can produce adsorption chelation to heavy metal ions to form stable chelates, and this chelation can effectively realize the fixation of heavy metal ions, thereby greatly reducing the residual metal ions.

[0031] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. DETAILED DESCRIPTION

[0032] The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] A flocculant is prepared from the following raw materials in parts by weight:

[0035]

[0036] The preparation method of the flocculant comprises the following steps:

[0037] The first step is to weigh each raw material according to weight and set aside;

[0038] The second step is to put the modified polyaluminium chloride, cross-linked sepiolite and modified sodium alginate into a mixer, stir and mix them evenly, transfer them into a ball mill, add polyoxyethylene polyoxypropylene ether and water, perform wet ball milling and mixing, discharge the materials, and dry them to obtain a flocculant.

[0039] Example 2

[0040] A flocculant is prepared from the following raw materials in parts by weight:

[0041]

[0042]

[0043] The preparation method of the flocculant comprises the following steps:

[0044] The first step is to weigh each raw material according to weight and set aside;

[0045] The second step is to put the modified polyaluminium chloride, cross-linked sepiolite and modified sodium alginate into a mixer, stir and mix them evenly, transfer them into a ball mill, add polyoxyethylene polyoxypropylene ether and water, perform wet ball milling and mixing, discharge the materials, and dry them to obtain a flocculant.

[0046] Example 3

[0047] A flocculant is prepared from the following raw materials in parts by weight:

[0048]

[0049] The preparation method of the flocculant comprises the following steps:

[0050] The first step is to weigh each raw material according to weight and set aside;

[0051] The second step is to put the modified polyaluminium chloride, cross-linked sepiolite and modified sodium alginate into a mixer, stir and mix them evenly, transfer them into a ball mill, add polyoxyethylene polyoxypropylene ether and water, perform wet ball milling and mixing, discharge the materials, and dry them to obtain a flocculant.

[0052] Comparative Example 1

[0053] A flocculant, which is different from Example 2 in that the cross-linked sepiolite is replaced by sepiolite, and is the same as Example 2 in other aspects.

[0054] Comparative Example 2

[0055] A flocculant, which is different from Example 2 in that the modified sodium alginate is replaced by sodium alginate, and the rest is the same as Example 2.

[0056] Comparative Example 3

[0057] A flocculant, which is different from Example 2 in that modified polyaluminium chloride is replaced by polyaluminium chloride, and the rest is the same as Example 2.

[0058] The modified polyaluminium chloride in the above examples and comparative examples was prepared by the following preparation method:

[0059] Step S1, adding 1.2 g of 3-glycidyloxypropyltrimethoxysilane to a 5% hydrochloric acid solution, hydrolyzing for 8 h, adding 5 g of polyaluminium chloride, adjusting the pH to 10 with a 0.1 mol / L sodium hydroxide solution, stirring at 65° C. for 6 h, discharging the material to obtain an intermediate material;

[0060] Take 0.2g of the intermediate material and perform a titration test using the hydrochloric acid acetone method to calculate the epoxy value of the intermediate material, and the result is 3.514mmol / g;

[0061] Step S2, 4.5g of the intermediate material, 12g of chitosan and 2% acetic acid solution are mixed, mechanically stirred evenly, and heating is turned on. When the temperature rises to 60°C, the temperature is kept unchanged, stirred for 3h, cooled and discharged, and modified polyaluminium chloride can be obtained.

[0062] In step S2, the molecular weight of the chitosan is 500,000 and the degree of deacetylation is 95%.

[0063] Take 0.2g of modified polyaluminium chloride and use the hydrochloric acid acetone method again to measure the epoxy value. The result is 0.849mmol / g. This is because the primary amine in chitosan reacts with the epoxy groups of the intermediate material in the ring-opening addition, consuming a large amount of epoxy groups.

[0064] The cross-linked sepiolite in the above embodiments and comparative examples was prepared by the following preparation method:

[0065] Step SS1, adding a 0.4 mol / L sodium hydroxide solution dropwise to a 0.4 mol / L aluminum chloride solution, stirring at room temperature for 3 hours, and aging at room temperature for 24 hours to obtain a crosslinking agent mixture;

[0066] Step SS2, place 2g of sepiolite in a tubular furnace, calcine it at 400°C for 1h, take it out, let it cool naturally, add it to 25mL of cross-linking agent, control the temperature to 65°C, stir mechanically for 2h, stop heating, cool to room temperature and let it stand for hydrolysis for 16h to obtain cross-linked sepiolite.

[0067] The modified sodium alginate in the above examples and comparative examples was prepared by the following preparation method:

[0068] 3.2 g of sodium alginate was stirred and mixed with purified water to form a uniform solution, and then 1.2 g of dicyclohexylcarbodiimide and 0.4 g of N-hydroxysuccinimide were added to the solution, and stirred at room temperature for 30 min. Then, 1.5 g of dimethylpyridylamine was added to the solution. After the addition was completed, mechanical stirring was performed for 4 h, and the material was discharged and separated to obtain modified sodium alginate.

[0069] Take 0.5g of modified sodium alginate and use XKCHN-700 element analyzer to test the percentage of organic elements in the modified sodium alginate. The results show that the percentage of carbon element is 38.12% and the percentage of nitrogen element is 4.06%. Sodium alginate itself does not contain nitrogen element, so the nitrogen element comes from dimethylpyridinamine.

[0070] Test Case

[0071] Take the wastewater from a factory and test its COD to be 1219.2mg / L, turbidity to be 271.9NTU, Cu 2+ The concentration is 97.3mg / L, Pb 2+ The concentration is 83.697.3 mg / L. The flocculants prepared in Example 1 to Example 3 and Comparative Example 1 to Comparative Example 3 are added to the wastewater respectively, and the dosage is controlled to be 3 mg / L. After the addition is completed, the wastewater is mechanically stirred for 30 minutes and allowed to stand for 20 minutes. The flocculation effect of each flocculant is evaluated by testing the changes in various indicators before and after the wastewater treatment. The test results are recorded in Table 1:

[0072] Table 1 - Test results

[0073] COD removal rate / % Turbidity reduction rate / % <![CDATA[Cu 2+ Removal rate / %]]> <![CDATA[Pb 2+ Removal rate / %]]> Example 1 63.8 91.3 99.2 97.8 Example 2 64.2 91.5 99.6 98.3 Example 3 64.1 91.3 99.5 98.0 Comparative Example 1 56.1 83.7 93.1 90.6 Comparative Example 2 61.9 87.1 86.5 82.1 Comparative Example 3 46.4 68.9 83.8 75.9

[0074] The results show that the flocculants made of modified polyaluminium chloride, cross-linked sepiolite and modified sodium alginate as the main raw materials have a good flocculation effect on pollutants in water bodies. After conventional sepiolite is used to replace cross-linked sepiolite, it is difficult to achieve efficient flocculation within 20 minutes due to its small specific surface area and weak adsorption capacity. After the modified sodium alginate is replaced by conventional sodium alginate, the removal ability of the heavy metal ions of the flocculant is obviously weakened. After the modified polyaluminium chloride is replaced by conventional polyaluminium chloride, the bridging effect is lost, and it is difficult to form dense aggregates, resulting in a weakened flocculation ability.

[0075] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.

[0076] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a flocculant for sewage treatment, characterized in that: The flocculant is made from the following raw materials in parts by weight: The preparation method comprises the following steps: The first step is to weigh each raw material according to weight and set aside; The second step is to put the modified polyaluminium chloride, cross-linked sepiolite and modified sodium alginate into a mixer, stir and mix them evenly, then transfer them into a ball mill, add polyoxyethylene polyoxypropylene ether and water, perform wet ball milling and mixing, discharge the materials, and dry them to obtain a flocculant; The specific preparation method of the modified polyaluminium chloride is as follows: Step S1, adding 3-glycidyloxypropyltrimethoxysilane to a hydrochloric acid solution with a mass fraction of 5%, hydrolyzing for 6-9 hours, adding polyaluminium chloride, adjusting the pH to 9-10 with sodium hydroxide solution, stirring at 60-70° C. for 4-6 hours, discharging the material to obtain an intermediate material; Step S2, mixing the intermediate material, chitosan and 1-2% acetic acid solution by mass, mechanically stirring evenly, turning on the heating, and when the temperature rises to 50-60° C., keeping the temperature unchanged, stirring for 2-4 hours, cooling and discharging the material, and then obtaining modified polyaluminium chloride; The preparation method of the cross-linked sepiolite is as follows: Step SS1, adding a sodium hydroxide solution with a concentration of 0.2-0.4 mol / L dropwise to an aluminum chloride solution with a concentration of 0.3-0.5 mol / L, stirring at room temperature for 2-4 hours, and aging at room temperature for 12-24 hours to obtain a crosslinking agent mixture; Step SS2, placing the sepiolite in a tube furnace, calcining it at a temperature of 400-450° C. for 1-2 hours, taking it out, allowing it to cool naturally, adding it to a crosslinking agent, controlling the temperature to 60-70° C., mechanically stirring for 1-3 hours, stopping heating, cooling it to room temperature, and standing it for hydrolysis for 12-18 hours to obtain crosslinked sepiolite; The preparation method of the modified sodium alginate is as follows: Sodium alginate and purified water are stirred and mixed to form a uniform solution, and then the composite catalyst is added to the solution, and stirred at room temperature for 20-40 minutes. Then, dimethylpyridylamine is added to the solution. After the addition is completed, mechanical stirring is performed for 3-6 hours, and the material is discharged and separated to obtain modified sodium alginate; The composite catalyst is dicyclohexylcarbodiimide and N-hydroxysuccinimide in a mass ratio of 1:0.3-0.

4.

2. The method for preparing a flocculant for sewage treatment according to claim 1, characterized in that: In step S1, the concentration of the sodium hydroxide solution is 0.1-0.2 mol / L.

3. The method for preparing a flocculant for sewage treatment according to claim 1, characterized in that: In step S2, the molecular weight of the chitosan is 400,000-500,000, and the degree of deacetylation is 80-95%.

4. The method for preparing a flocculant for sewage treatment according to claim 1, characterized in that: In step SS2, the solid-to-liquid ratio of the sepiolite and cross-linking agent mixed solution is 1 g:10-15 mL.

5. A flocculant for sewage treatment, characterized in that: The flocculant is prepared by the method for preparing the flocculant as claimed in claim 1.